Pituitary tumor diagnosis using gadolinium-enhanced magnetic resonance imaging in a dog with hyperadrenocorticism. A case report (2006)
ABSTRACT: Cushing’s disease is a common endocrine disorder of dogs, caused by persistent high concentration of cortisol in circulating blood. Almost eighty five percent of the cases of spontaneous hyperadrenocorticism in dogs are the result of a functional pituitary tumor or hyperplasia. Advanced imaging techniques like computed tomography (CT) or magnetic resonance imaging (MRI) are the best means to obtain a diagnosis of a pituitary tumor in dogs with pituitary-dependent hyperadrenocorticism (PDH). Moreover these imaging techniques are required to asses the size and location of the pituitary tumor when planning surgical removal of the tumor mass or of the complete pituitary gland. In Colombia, the use of these imaging techniques is very limited in the small animal practice, but it has recently become available for veterinary patients thanks to agreements with human clinical institutions. This report describes the case of an eleven year-old golden retriever with PDH as a result of a functional pituitary tumor, visualized by magnetic resonance imaging using gadolinium as contrast agent.